Determinants of tax compliance intention on withholding taxes among payers in Klang Valley - Siti Fatma Zuhra, Din (2023)
This study attempted to investigate the determinants of tax compliance intention in with holding tax in Klang Valley. A theoretical framework was developed based on the theory of planned behavior and economic deterrence model of tax compliance. The objectives of the study were to determine the level and relationship of attitude, subjective norms, and perceived behavioral control (clarity of law, tax knowledge and probability audit) towards tax compliance intention in a withholding tax among payers in Klang Valley. Online questionnaires were used for data collection. Reliability analysis, factor analysis, descriptive analysis, and multiple regression analysis were conducted using the data collected from 71 respondents chosen via random sampling. The results of multiple regression analysis showed that independent variables that significantly influence the intention towards tax compliance are attitude, tax knowledge and probability of audit. The findings also revealed that the independent variables tested explained 80.9% of the variance in tax compliance intention in withholding tax. Hence, the model used in this study was supported as suitable and was able to predict the dependent variable, tax compliance intention.